اللافتات التوجيهية ودورها في تسهيل حركة التنقل على مستوى المحاور المهيكلة لمدينة المسيلة - بلوط, سلسبيل (University of Msila, 2025)
تعد اللافتات التوجيهية من أهم الوسائل التنظيمية في الفاء الحضري، خاصة على مستوى المحاور المهيكلة، حيث تساهم بشكل فعال في تسهيل حركة التنقل وتنظيم تدفق المرور. فهي تزود مستعملي الطريق بالمعلومات الضرورية لاتخاذ قرارات تنقل سليمة، وتقلل من التوقفات المفاجئة والارتباك المروري، مما ينعكس إيجابا على انسيابية الحركة والسلامة الطرقية. وتزداد أهمية هذه اللافتات في المحاور ذات الكثافة العالية، التي تربط بين الأحياء والمراكز الحضرية الرئيسية، إذ يمكن للتخطيط الجيد لمواقعها، واعتماد معايير واضحة في تصميمها، أن يحسن أداء شبكة النقل بشكل عام ويعزز من فعالية البنية التحتية للمدينة.

Directional signs are considered one of the most important organizational tools in urban space,especially along structured cooridors, they play an active role in facilitating mobility and regulating traffic flow by providing road users with essential information for making safe travel decisions.this helps reduce sudden stops and confusion on the road,which positively impacts the smoothness of movement and road safety.The importance of these signs increases in high_density corridors that connect neighborhoods and major urban centers.proper planning of their location and the adoption of clear design standards can enhance the overall performance of the transport network and sttrengthen the effectiveness of the city’s infrastructur.
Keywords: اللافتات التوجيهية; المحاور المهيكلة; مدينة المسيلة; حركة المرور